Temporal Loudness Weights Are Frequency Specific - Fischenich, Alexander; Hots, Jan; Verhey, Jesko; Oberfeld, Daniel (Frontiers in Psychology, 2021)
Previous work showed that the beginning of a sound is more important for the perception of loudness than later parts. When a short silent gap of sufficient duration is inserted into a sound, this so-called “primacy effect” reoccurs in the second sound part after the gap. The present study investigates whether this temporal weighting occurs independently for different frequency bands. Sounds consisting of two bandpass noises were presented in four different conditions: (1) a simultaneous gap in both bands, (2) a gap in only the lower frequency band, (3) a gap in only the higher frequency band, or (4) no gap. In all conditions, the temporal loudness weights showed a primacy effect at sound onset. For the frequency bands without a gap, the temporal weights decreased gradually across time, regardless of whether the other frequency band did or did not contain a gap. When a frequency band contained a gap, the weight at the onset of this band after the gap was increased. This reoccurrence of the primacy effect following the gap was again largely independent of whether or not the other band contained a gap. Thus, the results indicate that the temporal loudness weights are frequency specific.